King Arthur : a casebook - Kennedy, Edward Donald (New York : Routledge, 2002)
A collection of sixteen essays that examine Arthurian tales written in English, French, Latin, and German and trace the evolution of the legend through the centuries.
Includes bibliographical references.
Adult
Keywords: Arthurian romances -- History and criticism; Arthurian romances -- History and criticism